Effects of a health-educational and psychological intervention on socio-cognitive determinants of skin protection behaviour in individuals with occupational dermatoses - Matterne, Uwe; Diepgen, Thomas L.; Weisshaar, Elke (International archives of occupational and environmental health, 2010)
Occupational skin diseases are a significant public health concern. Little is known about the cognitive representations individuals with occupational skin disease have towards measures of personal skin protection and occupational safety and whether they change during an intervention. We aimed to evaluate whether social cognitions as embodied by the theory of planned behaviour become more favourable during a tertiary inpatient individual prevention programme (TIP) and whether the model’s predictions hold in a setting to which the model has not been applied.